2019
DOI: 10.22460/project.v2i3.p377-384
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Lexical Cohesion Found in “Never Say Never” Song Lyrics

Abstract: The purpose of this study is to describe kinds of lexical cohesion and to know frequent lexical cohesion used to support the cohesiveness of discourse in Justin Bieber and Jaden Smith’s song entitled “Never Say Never”. The subject of this study is “Never Say Never” song lyrics. This study uses descriptive qualitative that focuses on lexical cohesion in particular synonym, repetition (anaphora and epistrophe repetition) and antonym. The instrument that the researchers used are books, earphone, youtube and other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…It proved that the word I in one part or sentence is repeated many times, it might seem that the songwriter wants to emphasize the main character which is the singer to be the focus. The repetition in the song is very common occurred in the song lyrics, it is proven by Pratiwi et al (2019) in their research that repetition is the highest number from all lexical cohesion devices, and they stated that the many repetitions occurred in the song because the songwriter wants to create a good rhythm.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It proved that the word I in one part or sentence is repeated many times, it might seem that the songwriter wants to emphasize the main character which is the singer to be the focus. The repetition in the song is very common occurred in the song lyrics, it is proven by Pratiwi et al (2019) in their research that repetition is the highest number from all lexical cohesion devices, and they stated that the many repetitions occurred in the song because the songwriter wants to create a good rhythm.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the word woman became the meronym of the word mama. The fourth cohesive device is antonym that literally can be interpreted as the word or name of things that have the opposite meaning (Pratiwi et al, 2019). The song lyrics of Coke Bottle did not show the word that is included as the antonym.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are different types of research and one of them is "descriptive analytical." According to Tavakoli in (Pratiwi et al, 2019) data analysis is "the process of reducing accumulated data collected in research to a manageable size, developing summaries, and looking for patterns. While interpreting means an explanation or conceptualization by a critic of a work of literature, painting, music, or other art form; an exegesis (Ardhyanti & Supriyatiningsih, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…This can be proven from several related studies. For instance, Pratiwi, Jayanti, and Syathroh (2019), in their research, only focused on lexical cohesion in repetition, synonym, and antonym. They revealed that synonym is the most dominant set after repetition.…”
Section: Synonymmentioning
confidence: 99%